Trust Transfer on the World Wide Web - Stewart, Katherine J. (Organization Science, 2003)
The World Wide Web (WWW) has been touted as providing great opportunities for small businesses to compete and thrive. Concerns about trust have been identified as a barrier to such businesses' success. This research explores how consumers' initial trust judgments about organizations they encounter on the Web may be influenced by hypertext links from trusted websites and associations with the more trust-inducing traditional retail channel. This paper develops and tests a cognitive model of the trust transfer process, arguing that trust is transferred across hypertext links based on the perceived interaction and similarity of the linked organizations, and that institution-based trust is transferred from the traditional shopping channel to a Web-based organization based on evidence that the Web-based organization has a physical store. An experimental study shows that a hypertext link from one website to another increased the extent to which the linked organizations were perceived to have a business relationship and be similar, and these perceptions had a positive influence on trusting beliefs regarding the linked site. Associating with the physical shopping channel by showing a picture of a building on a website increased the extent to which subjects reported intention to buy from the site. The study provided empirical evidence that trusting beliefs regarding the website had a significant positive effect on intention to buy from it. This paper discusses further development of the trust transfer model based on the social perception literature and explores implications for future research.